Influence of asymmetric out-of-roundness coupled with wear of subway wheels on vehicle dynamics. (July 2021) - Zhu, Aihua; Li, Hongxiao; Yang, Jianwei; Li, Qiang; Yang, Si; Fu, Caozheng
Out-of-roundness and tread wear are common types of damage to subway wheels, which greatly affect the dynamic performance of subway vehicles. In light of the coupling and asymmetry of out-of-roundness and tread wear found in real-world subway wheels, an analysis method that considers asymmetric out-of-roundness coupled with tread wear was proposed for vehicle dynamics. A vehicle dynamics model featuring asymmetric out-of-roundness coupled with tread wear was used to investigate the influences of asymmetric wheel damage and coupled damage on the dynamic performance of the vehicle system. The vehicle's dynamic performance was simulated under different conditions, including asymmetric out-of-roundness and symmetric out-of-roundness, uncoupled damage and coupled damage, asymmetric coupled damage and symmetric coupled damage. Then the estimated data was compared against the measured data. The study finds that the vertical wheel/rail contact force, lateral wheel/rail contact force, derailment coefficient and wheel unloading rate increased in the case of asymmetric out-of-roundness. In the presence of coupled damage, the degree of tread wear had a relatively great influence on the lateral wheel/rail contact force, axle lateral force, and derailment coefficient, but had little influence on the vertical contact force. Compared to symmetric coupled damage, asymmetric coupled damage had a greater influence on peak vertical vibration acceleration and stability index, and their values are closer to the measured values in the case of asymmetric coupled damage. This suggests that the dynamics model that considers asymmetric out-of-roundness coupled with tread wear can provide more accurate results as guidance on the maintenance and overhaul of subway wheels.